Association between mental health, subjective income status, perceived parental and peer support, and substance use in icelandic college students - Sonja M. Júlíusdóttir Jacobsen 1996- (2020)
Substance use among adolescents has been a growing concern for decades. Researchers have tried to understand what might lead to usage in hopes of preventing it. Internal and external factors have been researched throughout the years as a cause of substance use in adolescents by assessing what might be a risk or protective factor. The current study was conducted using data from a nationally representative study conducted by the Icelandic Centre for Social Research & Analysis. Participants were 2129 college students in Iceland. The study aimed to investigate how mental health, subjective income status, parental- and peer support, a combination of internal and external factors, might encourage substance use in adolescents. Regression was used to assess the relationship between substance use and all variables. Results showed that all variables had a significant relationship with substance use which is consistent with previous studies. Having good mental health, receiving parental support, and coming from a home with average or higher income were all protective factors for substance use whilst peer support appeared to be a risk factor. Results show the importance of supporting adolescents that come from poverty, do not receive support from parental figures, or are struggling with mental illnesses. Keywords: substance use, adolescents, mental health, support, subjective income status Vímuefnanotkun unglinga hefur lengi verið áhyggjuefni. Rannsakendur hafa reynt að varpa ljósi á þá áhrifaþætti sem gætu átt þátt í því að unglingar sækist í vímuefni í þeirri von um að koma í veg fyrir það. Innri og ytri áhrifaþættir hafa verið rannsakaðir í gegnum árin sem orsök vímuefnaneyslu með því markmiði að meta hvað gætu verið áhættu- og verndandi þættir. Notast var við gögn frá Rannsóknir & Greining þar sem spurningalisti var sendur til franhaldsskóla á Íslandi en þátttakendur voru 2129 talsins. Tilgangur rannsóknar var að rannsaka hvernig andleg heilsa, fjárhagsstaða, stuðningur foreldra og vina gætu haft áhrif á ...